Sustainable Organizational Transformation - Knez, Matjaž (Mastering Sustainability in Supply Chains, 2026)
Sustainability has become an essential part of business strategies around the world, as companies discover how green approaches strengthen their financial and market positions. Implementing sustainable practices leads to greater profitability by ensuring efficiency and innovation, which reduce costs and create new opportunities. Companies that comply with environmental standards and legislation often go beyond minimum requirements, which brings advantages in reducing risks and building a brand that reflects social responsibility and ethics. Effective planning for sustainable transformation requires a careful assessment of the current situation, setting SMART goals, and developing a strategy that leads to truly sustainable operations. In the following text, we will explore how companies move through the different stages of sustainable transformation, from committing to action to fully integrating sustainability into the core of the business model.